2021
DOI: 10.2147/jhc.s289955
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Hepatocellular Carcinoma After Start of Treatment for Chronic Hepatitis C Remain High with Direct Acting Antivirals: Analysis from a Swiss Liver Transplant Center

Abstract: Background Direct-acting antivirals (DAA) have revolutionized the therapy of chronic hepatitis C (CHC) and have replaced previous PEG-interferon/ribavirin (PEG-IFN/RBV) treatment. Patients with CHC and advanced liver disease are at increased risk for hepatocellular carcinoma (HCC). However, the effects of DAA-based CHC treatment on subsequent HCC incidence remain poorly understood. Patients and Methods This retrospective single-institution cohort study included 243 cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Controlled studies showed similar results. Higher recurrence or occurrence rates were reported in patients treated with DAAs compared with IFN treatment [40][41][42] .…”
Section: Daas Vs Ifnmentioning
confidence: 96%
“…Controlled studies showed similar results. Higher recurrence or occurrence rates were reported in patients treated with DAAs compared with IFN treatment [40][41][42] .…”
Section: Daas Vs Ifnmentioning
confidence: 96%
“…A retrospective cohort study was carried out on 243 consecutive HCV patients who received PEG-IFN/RBV and were followed for a median of 9.3 years, and 263 HCV patients who received DAA treatment and were followed for a median of 4.1 years. It revealed that a considerably increased hazard was associated with DAA treatment[ 60 ]. A French study conducted on 1270 HCV patients revealed that, the differences of the occurrence of HCC after IFN and DAA regimens could be explained by the higher prevalence of Child-Pugh class B, portal hypertension, and diabetes among DAA-treated patients vs IFN-induced SVR patients.…”
Section: Impact Of Direct-acting Antiviral Regimens On Hcv Infectionmentioning
confidence: 99%
“…The higher rate of HCC after DAA therapy may be because they are the drugs of choice for treating old patients and those with liver cirrhosis and end-stage liver disease as IFN was not indicated to treat such patients[ 62 ]. The possible clarification of the elevated incidence of HCC after the start of DAA therapy, might be the change in the growth of pre-existing subclinical and undetectable HCC upon DAA treatment[ 60 ]. A high HCC risk after DAA treatment was also reported, especially in individuals with uncharacterized liver nodules[ 63 ].…”
Section: Impact Of Direct-acting Antiviral Regimens On Hcv Infectionmentioning
confidence: 99%